Confronting ethical challenges in long-term research programs in the tropics. (March 2021) - Seidler, Reinmar; Primack, Richard B.; Goswami, Varun R.; Khaling, Sarala; Devy, M. Soubadra; Corlett, Richard T.; Knott, Cheryl D.; Kane, Erin E.; Susanto, Tri Wahyu; Otali, Emily; Roth, Robin J.; Phillips, Oliver L.; et al.
Abstract: Ecologists and conservation biologists conducting long-term research programs in the tropics must confront serious ethical challenges that revolve around economic inequalities, cultural differences, supporting the local communities as much as possible, and sharing the knowledge produced by the research. In this collective article, researchers share their experiences and perspectives in dealing with the ethical issues that arise during research activities and cannot be ignored. Highlights: Long-term research programs in the tropics confront ethical challenges revolving around economic inequalities and cultural differences. In 9 short essays, experienced researchers offer perspectives on ethical questions that arise during research activities. Three principal responsibilities of researchers working in another country and culture are to understand cultural differences and adapt to them as much as possible, to be sure the research project brings added value to the local community, to share the resulting information and knowledge with local people, students, the scientific community, and government agencies. Locations range across the global tropics.